Implementation of the "Jemput Bola" Program for Heirs' Certificate (Jebol Keris) as an Innovation in Administrative Services in Mayangan District, Probolinggo City - Istiqomah, Riska Nur; Sucahyo, Imam; Septiandika, Verto (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
Humans as legal subjects are always connected to the administrative process with civil law from birth to death. Even in society, it also takes care of the existence of inheritance rights for heirs. However, the process of imposing inheritance rights is not easy and can cause conflict. So that the entire process of the rights and obligations of the heirs can be carried out with a certificate of inheritance rights. The issuance of suket heirs involves the Subdistrict and Kelurahan as officials who witness and certify. As in Mayangan Sub-district, Probolinggo City, to improve public services in special administration of heirship certificates in order to minimize conflicts and have complete and official data. Mayangan Sub-district of Probolinggo City implemented the Jebol-Keris innovation (Jemput Bola Surat Keterangan Ahli Waris). This is interesting to research. The research used is qualitative research, while the method uses descriptive methods. The research focus is in accordance with the Decree of the Minister of PAN Number: 63/KEP/M.PAN/7/2003. The results showed that the Jebol Keris program in Mayangan Subdistrict was running in accordance with service standardization starting from procedures, time, costs, products, infrastructure, and employee competence in issuing heirship certificates.